Nonphotodynamic Roles of Methylene Blue: Display of Distinct Antimycobacterial and Anticandidal Mode of Actions. (31st January 2018) - Pal, Rahul; Ansari, Moiz A.; Saibabu, Venkata; Das, Shrayanee; Fatima, Zeeshan; Hameed, Saif
Abstract : Significance of methylene blue (MB) in photodynamic therapy against microbes is well established. Previously, we have reported the antifungal potential of MB against Candida albicans . The present study attempts to identify additional antimicrobial effect of MB against another prevalent human pathogen, Mycobacterium tuberculosis (MTB). We explored that MB is efficiently inhibiting the growth of Mycobacterium at 15.62  μ g/ml albeit in bacteriostatic manner similar to its fungistatic nature. We uncovered additional cell surface phenotypes (colony morphology and cell sedimentation rate) which were impaired only in Mycobacterium . Mechanistic insights revealed that MB causes energy dependent membrane perturbation in both C. albicans and Mycobacterium . We also confirmed that MB leads to enhanced reactive oxygen species generation in both organisms that could be reversed upon antioxidant supplementation; however, DNA damage could only be observed in Mycobacterium . We provided evidence that although biofilm formation was disrupted in both organisms, cell adherence to human epithelial cells was inhibited only in Mycobacterium . Lastly, RT-PCR results showed good correlation with the biochemical assay. Together, apart from the well-established role of MB in photodynamic therapy, this study provides insights into the distinct antimicrobial mode of actions in two significant human pathogens, Candida and Mycobacterium, which can be extrapolated to improve our understanding of finding novel therapeutic options.